2020
DOI: 10.2147/ott.s233338
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA circHUWE1 Is Upregulated and Promotes Cell Proliferation, Migration and Invasion in Colorectal Cancer by Sponging miR-486</p>

Abstract: Background: Emerging studies have revealed that circular RNAs (circRNAs) correlate with diverse diseases including cancers. However, little is known about the functions of circRNAs in colorectal cancer (CRC). In our previous research, downregulation of hsa_circ_0140388 (circHUEW1) has been detected in CRC tissues through highthroughput sequencing. However, the underlying mechanism by which circHUWE1 regulates the proliferation and apoptosis in CRC has not been investigated. Materials and Methods: The levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Therefore, there is a clinical need for an improved tumor biomarker for the diagnosis of CRC. Compare to some other researches of circRNAs, hsa_circ_0002320 has higher sensitivity and specificity for the diagnosis of CRC [ 22 24 ]. With the development of liquid biopsy tools and other clinical techniques [ 25 , 26 ], circSPARC is expected to be a new biomarker for the prognosis and early diagnosis of CRC.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, there is a clinical need for an improved tumor biomarker for the diagnosis of CRC. Compare to some other researches of circRNAs, hsa_circ_0002320 has higher sensitivity and specificity for the diagnosis of CRC [ 22 24 ]. With the development of liquid biopsy tools and other clinical techniques [ 25 , 26 ], circSPARC is expected to be a new biomarker for the prognosis and early diagnosis of CRC.…”
Section: Discussionmentioning
confidence: 88%
“…8 CircRNA circHUWE1 knockdown inhibits growth and metastasis of colorectal cancer cells through targeting miR-486. 9 circRIP2 promotes bladder cancer cell proliferation, migration and invasion by regulating miR-1305/Tgf-β2/smad3 axis. 10 In addition, hsa_circ_001680 regulates growth and metastasis in colorectal cancer cells and affects chemoresistance through miR-340/BMI1 axis.…”
Section: Introductionmentioning
confidence: 99%
“…This new area of research is extra attractive for their applications in clinical practice as tumor marker or molecular therapeutic targets are possible (24)(25)(26). In a few available studies, circRNAs are reported to play the role of oncogene or tumor suppressor gene, affecting the occurrence of tumors development, such as lung squamous cell carcinoma, colorectal cancer, hepatocellular carcinoma, thyroid cancer, and so on (27)(28)(29)(30). However, there have been little studies on circRNAs in gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 99%